A qualitative exploration of body image experiences of women progressing through pregnancy. Issue 1 (February 2016) - Watson, Brittany; Broadbent, Jaclyn; Skouteris, Helen; Fuller-Tyszkiewicz, Matthew
Abstract: Background: Pregnancy provides an interesting challenge to body image theories in that the natural physiological changes push women further from the socioculturally prescribed thin ideal which these theories hinge upon. The impact that these significant physiological changes have on the woman's body image during pregnancy may depend on the extent to which they retain or revise the ideal. However, little is known about body image experiences during pregnancy. Aim: To provide a comprehensive exploration of the body image experiences of pregnant women. Methods: Individual structured interviews were conducted with 19 currently pregnant women. Transcriptions were analysed using a thematic content analysis approach. Findings: Themes extracted from the qualitative data included: (1) women's body image experiences during pregnancy were complex and changing, and shaped by the salience of specific body parts, the women's expectations for future changes to their body within the perinatal period, the functionality of the body, and their experience of maternity clothing, (2) women were able to negotiate the changes to their bodies as they recognised the functionality of the pregnant body, (3) women were surprised by the public nature of the pregnant body, (4) partner support and positive feedback about the pregnant body was highly valued, and (5) the importance of open communication around weight and body image in antenatal healthcare. Discussion: Our findings highlight the need for the adaptation and expansion of existing body image theories to be used as a framework for women's experiences of pregnancy.